Determination of Aedes Spp. Mosquito Breeding Spots as a High-Risk Area Through Maya Index Analysis in Way Halim Bandar Lampung - Athiyya Nurfadhilah; Emantis Rosa; M. Kanedi; Tugiyono Tugiyono (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
Dengue Haemorrhagic Fever (DHF) is a disease that is transmitted through the Aedes aegypti and Aedes albopictus mosquito vectors. The Maya index (MI) is an indicator to identify whether an area is at high risk as a breeding site for mosquitoes. This study aims to determine the types of breeding places and types of mosquito larvae of DHF and MI vectors in the Way Halim District of Bandar Lampung. The method used was a survey method on 100 houses in 5 villages in Way Halim District, namely Jaga Baya 1, Jaga Baya 2, Jaga Baya 3, Way Halim Permai, and Gunung Sulah. Data analysis to determine MI uses the Breeding Risk Index (BRI) and Hygiene Risk Indicator (HRI) indicators. The results of this study indicate that there were 225 containers inside the house observed, where 51 containers of them were found to have Aedes mosquito larvae while outside the house found as many as 28 containers with 8 containers including larvae. The identification results found 2 types of Aedes mosquitoes namely, Ae. aegypti (88.24%) and Ae. albopictus (11.76%). The results of the MI analysis show that Way Halim District is classified as a District with a moderate MI category with an MI value of 46%